Iowa RBA, October 23-26, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Iowa RBA update for October 23-26, 1995. Highlights of the update include sightings of a Scissor-tailed Flycatcher, Mew Gull, a female Black Scoter, MacGillivray's Warbler, Red Phalarope and an adult Pacific Loon. Also included are handwritten notes for the next week's update with sightings of a Common Loon and a Horned Grebe. Epson - sheet feed/flatbed